Effects of intestinal microbiota on pharmacokinetics of cyclosporine a in rats - Zhou, Jinping; Zhang, Rui; Guo, Pengpeng; Li, Peixia; Huang, Xixi; Wei, Ye; Yang, Chunxiao; Zhou, Jiali; Yang, Tingyu; Liu, Yani; Shi, Shaojun (Frontiers in Microbiology, 2022)
Background Intestinal microbiota has been confirmed to influencing the pharmacokinetic processes of a variety of oral drugs. However, the pharmacokinetic effects of the gut microbiota on cyclosporine A, a drug with a narrow therapeutic window, remain to be studied. Method Twenty-one rats were randomly divided into three groups: a) control group (CON), b) antibiotic treatment group (ABT) and c) fecal microbe transplantation group (FMT). The ABT group was administrated with water containing multiple antibiotics to deplete microorganisms. FMT was with the same treatment, followed by oral administration of conventional rat fecal microorganisms for normalization. Result The bioavailability of CSA increased by 155.6% after intestinal microbes were consumed by antibiotics. After intestinal microbiota reconstruction by fecal transplantation, the increased bioavailability was significantly reduced and basically returned to the control group level. Changes in gut microbiota alter the protein expression of CYP3A1, UGT1A1 and P-gp in liver. The expressions of these three proteins in ABT group were significantly lower than those in CON and FMT groups. The relative abundance of Alloprevolleta and Oscillospiraceae UCG 005 was negatively correlated with CSA bioavailability while the relative abundance of Parasutterella and Eubacterium xylanophilum group was negatively correlated with CSA bioavailability. Conclusion Intestinal microbiota affects the pharmacokinetics of CSA by regulating the expression of CYP3A1, UGT1A1 and P-GP.